2006
DOI: 10.1590/s0100-879x2006000600011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stress on catecholamine stores in central and peripheral tissues of long-term socially isolated rats

Abstract: Both the peripheral sympatho-adrenomedullary and central catecholaminergic systems are activated by various psycho-social and physical stressors. Catecholamine stores in the hypothalamus, hippocampus, adrenal glands, and heart auricles of long-term socially isolated (21 days) and control 3-month-old male Wistar rats, as well as their response to immobilization of all 4 limbs and head fixed for 2 h and cold stress (4ºC, 2 h), were studied. A simultaneous single isotope radioenzymatic assay based on the conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…As a result, we detected reduced brain NE concentrations after SI. This agrees with the findings of previous studies in which the brain NE concentrations of isolated animals were found to be significantly lower than those of the control groups [29,30]. Reductions in brain NE concentrations are associated with anxiety and depressive symptoms [31,32].…”
Section: Discussionsupporting
confidence: 92%
“…As a result, we detected reduced brain NE concentrations after SI. This agrees with the findings of previous studies in which the brain NE concentrations of isolated animals were found to be significantly lower than those of the control groups [29,30]. Reductions in brain NE concentrations are associated with anxiety and depressive symptoms [31,32].…”
Section: Discussionsupporting
confidence: 92%
“…The mechanism of action of POEE appears to involve D 1 dopamine and ␤-noradrenergic receptors, since SCH23390 and propranolol reverse POEE effects on both the tail suspension and forced swimming tests (Piato et al, submitted). There is evidence that both noradrenergic (Sherman and Petty, 1980) and dopaminergic neurotransmission (Harvey et al, 2005;Dronjak and Gavrilovic, 2006) may be altered by stress in certain brain areas, including the hippocampus. While additional evidence is required to elucidate the role of the hippocampus in adaptation to stress, an attenuation of the stress-induced aversive state and consequent emotional impact has been suggested (Tsankova et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the first method, movements are restricted by placing animals in an appropriately sized animal holder (121). The second technique requires animals to be immobilized by stretching and fixing their limbs to an underlying board using adhesive tape; a metal loop coil restricts head movements (77). Different time periods have been used to model acute or chronic stresses (68,75,187).…”
Section: Animal Models Of Physical Stressmentioning
confidence: 99%